Iterative fragmentation improves the detection of ChIP-seq peaks for inactive histone marks - Laczik,M; Hendrickx,J; Veillard,A-C; Tammoh,M; Marzi,S; Poncelet,D (Bioinformatics and Biology Insights, 2016)
As chromatin immunoprecipitation (ChIP) sequencing is becoming the dominant technique for studying chromatin modifications, new protocols surface to improve the method. Bioinformatics is also essential to analyze and understand the results, and precise analysis helps us to identify the effects of protocol optimizations. We applied iterative sonication –- sending the fragmented DNA after ChIP through additional round(s) of shearing –- to a number of samples, testing the effects on different histone marks, aiming to uncover potential benefits of inactive histone marks specifically. We developed an analysis pipeline that utilizes our unique, enrichment-type specific approach to peak calling. With the help of this pipeline, we managed to accurately describe the advantages and disadvantages of the iterative refragmentation technique, and we successfully identified possible fields for its applications, where it enhances the results greatly. In addition to the resonication protocol description, we provide guidelines for peak calling optimization and a freely implementable pipeline for data analysis.